2017
DOI: 10.1016/j.jdermsci.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequencies of basophils, type 2 innate lymphoid cells and Th2 cells in skin of patients with atopic dermatitis but not psoriasis

Abstract: Background: Pathogenesis of atopic dermatitis (AD) involves interaction between type 2 cells that include basophils, mast cells, innate lymphoid type 2 cells (ILC2), and Th2 cells. Levels of IL-4 and IL-13 are elevated in AD patients. Objective: Here, we investigated the distribution of type 2 cells and the source of IL-4 and IL-13 in skin and blood of AD relative to psoriasis. Methods: Lesional skin biopsies and blood were collected from patients. Skin cell suspensions were prepared by mild enzymatic digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 36 publications
(51 reference statements)
4
76
0
Order By: Relevance
“…For example, basophils have been shown to play a role in the induction of inflammation in murine models of AD-like disease and have also been shown to promote optimal type 2 cytokine responses in a model of airway inflammation (64, 68). Consistent with these studies, basophils are increased in the lesional skin of patients suffering from AD and are elevated in the airways of patients suffering from asthma (68, 142). Moreover, murine studies have also demonstrated a non-redundant role for basophils in prompting the pathology associated with eosinophilic esophagitis (EoE)-like inflammation.…”
Section: Innate Immunitysupporting
confidence: 67%
“…For example, basophils have been shown to play a role in the induction of inflammation in murine models of AD-like disease and have also been shown to promote optimal type 2 cytokine responses in a model of airway inflammation (64, 68). Consistent with these studies, basophils are increased in the lesional skin of patients suffering from AD and are elevated in the airways of patients suffering from asthma (68, 142). Moreover, murine studies have also demonstrated a non-redundant role for basophils in prompting the pathology associated with eosinophilic esophagitis (EoE)-like inflammation.…”
Section: Innate Immunitysupporting
confidence: 67%
“…Interleukin‐4 and IL‐13 share IL‐4R α in their signaling cascades and induce similar biological responses. However, IL‐13 likely preferentially participates in peripheral tissues, including the skin, because tissue‐residing ILC2s produce IL‐13 but not IL‐4 . An IL‐13‐dominant microenvironment is evident in the lesional skin of AD, and the IL‐13‐rich local milieu causes barrier dysfunction by the down‐regulation of the OVOL1–FLG axis .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its production in Th2 cells, IL‐13 is produced in ILC2s . Mouse and human ILC2s are phenotypically comparable, lineage‐negative, non‐T and non‐B lymphocytes that produce high levels of IL‐13 and IL‐5 . Unlike IL‐13, no or only negligible IL‐4 is produced by ILC2s .…”
Section: Il‐13 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, substance P can initiate the release of IL‐3 and IL‐8, and various chemokines (eg, monocyte chemoattractant protein‐1 [MCP‐1], CCL‐5) . The significance of SP in inflammatory processes is further reflected by its increased expression in lesional skin of patients with AD, which concomitantly present elevated numbers of SP/NK 1 R + mast cells and basophils . Additionally, the chronic itching routinely observed in AD patients has been associated with SP, but not with mast cell function.…”
Section: Itch Mediators and Receptors With Links To Mast Cells And Bamentioning
confidence: 99%